TINJAUAN TENTANG TATA RIAS PENGANTIN KOTO NAN GADANG DI KOTA PAYAKUMBUH - Pebrianti, Yossi; Rahmiati, Rahmiati; Yanita, Merita (Journal of Home Economics and Tourism, 2017)
This research is begun from many changes that happened in the bridegroom’s clothing and makeup in the wedding procession in Payakumbuh. The goal of this research is to describe the bridegroom’s makeup from the makeup artists in Kenagarian Koto Nan Gadang Payakumbuh. This research is a descriptive research by using qualitative approach. The data collecting techniques used in this research are observation, interview and documentation. To obtain a valid and reliable data, the researcher doing data validity check such as participation extension, observation persistence, triangulation, peer checking and auditing. After the research is completed, the researcher discovers the Bridegroom’s makeup in Payakumbuh from the makeup artists in Kenagarian Koto Nan Gadang, Payakumbuh, West Sumatera, they are: 1) the makeup process of the Bridegroom in Koto Nan Gadang is different, started from applying foundation, eyebrow shaping, eye shadow smearing, nose shading, applying blush-on and lipstick smearing. 2) The clothes style for the bridegroom in Koto Nan Gadang is difference in many ways from the old styles, such as the groom that no longer wearing a coat. 3) The accessories used by the bridegroom is so different from the accessories they used in the old days, where dukuah kaba, and rago-rago are no longer used by the bridegroom. 4) Almost all of the makeup artists do not fully understand the old bridegroom’s clothes style and the meaning in each part of those clothes.Key words: observation, Bridegroom Makeup, Koto Nan Gadang